English as a Marker of Hierarchy in Classroom in Jaffna Schools: An Art-based Study - Vasanthakumar, S.J. (University of Jaffna, 2025)
This study explores how English language proficiency functions as a marker of hierarchy among secondary school students in the Jaffna district, irrespective of gender or school. It specifically investigates students’ perceptions of peers who are proficient in English, both inside and outside the classroom. Observations revealed that students who perform well in English— particularly those participating in English Day competitions or enrolled in bilingual classes—are often perceived as distinct from their peers. However, increased engagement with English language activities also appeared to result in social detachment from others. The research followed a qualitative, phenomenological methodology with an arts-based approach. Ten students were selected as the target group, and parental consent was obtained to ensure ethical participation and anonymity. Each student was asked to respond to a set of questions, provided in both Tamil and English, regarding their perceptions of classmates who are proficient or less proficient in English. Instead of traditional written responses, students were instructed to illustrate their views through drawings, accompanied by descriptive notes explaining their artwork. The students were subsequently interviewed by the researcher to clarify the meanings behind their use of colors and symbols. The collected data were analyzed thematically, using coding and symbol interpretation through an inductive approach. Labov’s theory of linguistic variation and social identity served as the theoretical framework for interpreting the findings. The analysis revealed that English proficiency does play a role in shaping classroom hierarchies. Students who were good at English were often portrayed as leaders or role models, receiving more attention and higher social status. In contrast, those with limited English skills were typically depicted as isolated or marginalized. This suggests that English functions not only as a communication tool but also as a symbol of social positioning and identity within the classroom context in Jaffna district schools.
Keywords: Hierarchy; ESL learners; Attitudes; Labov’s theory of linguistic variation; Social identity